A systematic review and meta-analysis expounding the relationship between methylene tetrahydrofolate reductase gene polymorphism and the risk of intracerebral hemorrhage among populations - Zou, Xue-Lun; Yao, Tian-Xing; Deng, Lu; Chen, Lei; Li, Ye; Zhang, Le (Frontiers in Genetics, 2022)
Background: The relationship between methylenetetrahydrofolate reductase (MTHFR) gene C677T and A1298C polymorphism with the risk of intracerebral hemorrhage (ICH) has remained to be controversial in recent years. This meta-analysis is aimed to confirm the association of these. Methods: Systematically searching the related studies from the PubMed, Embase, Cochrane Library, China national knowledge internet database from 1 January 1990 to 1 October 2020. The odd ratio (ORs) and 95% confidence interval (CIs) of gene-disease correlation in various gene models were calculated by fixed or random effect model of meta-analysis. We included 20 case-control studies in this meta-analysis with a total of 1,989 ICH patients and 4,032 health controls originated from Asian, Caucasian and African populations. Results: The statistical analysis demonstrated the association of MTHFR C677T gene polymorphism with ICH in allele model [ORT VS C=1.20 (95%CI: 1.06-1.36)]; homozygote model [OR TT VS CC=1.50 (95%CI: 1.20-1.88)]; dominant model [OR CT+ TT VS CC=1.23 (95%CI: 1.03-1.48)] and recessive model [ORTT VS CT+CC=1.37 (95%CI: 1.17-1.60)]. Besides, we also found the relationship of MTHFR C677T gene polymorphism with Asian in four comparison model (ORT VS C=1.19,95%CI:1.09-1.37, ORTT VS CC=1.46,95%CI: 1.15-1.85, OR CT+ TT VS CC =1.25,95%CI: 1.01-1.54, ORTT VS CT+CC=1.34,95%CI: 1.54-1.17) and Caucasian in four comparison model (ORT VS C=1.90,95%CI: 1.22-2.97, ORTT VS CC=2.67,95%CI: 1.42-5.00, OR CT+ TT VS CC =1.56,95%CI: 1.05-2.32, ORTT VS CT+CC=2.25,95%CI: 1.46-4.00). But no statistically significant correlation between A1298C polymorphism and the occurrence of ICH was detected in four studies. Conclusion: MTHFR C677T gene polymorphism increases the risk of ICH in Asian and Caucasian populations but has no impact on the incidence in African communities. More importantly, the risk of ICH increases in TT genotype individuals in comparison to CT and CC genotype individuals in Asian and Caucasian populations.